First-principles study of origin of perpendicular magnetic anisotropy in MgO|CoFeB|Ta structures - Yanjie Wang; Xiaoyuan Nie; Junhui Song; Chao Wang; Fan Yang; Yaodan Chi; Xiaotian Yang; Ye Shen; Chunyan Xu (Results in Physics, 2023)
Using fist-principles calculations, we study the B atom of diffusion process and the origin of the perpendicular magnetic anisotropy in MgO|CoFe|Ta structures with boron. It is found that B atoms are more likely to enter the Ta layer than FeCo layer and MgO layer. This result is in good agreement with that of the experimental and theoretical results. Furthermore, we elucidate the physical origin of the interfacial PMA Ta|CoFe|MgO structure with B element. We find that interfacial PAM come from both the MgO|CoFe and CoFe|Ta layer interfaces. These findings provide a comprehensive understanding of the PMA and point towards the possibility to achieve the advanced-node STT-MRAM with high thermal stability.